A feasibility study of solar energy in South Korea. (September 2017) - Nematollahi, Omid; Kim, Kyung Chun
Abstract: Through the years using renewable energies become one of the interesting issues in each country. Among the renewable energies, solar energy is more attractive. Governments planned to install more solar power plants. Feasibility study is an important step of every solar energy project. This paper investigates the feasibility of using solar energy in different regions of South Korea. For this purpose, the maximum, minimum, and average values of yearly horizontal radiation were calculated for 24 stations for a five-year period. Monthly and annual clearness indices for these stations were then calculated. The annual average horizontal radiation map and Geographic Information Systems (GIS) maps of global horizontal radiation were prepared for each month of the year. Maps were then prepared for the annual average of monthly mean clearness index for the 24 stations. Furthermore, the sunshine hours were presented for 78 stations for a three-year period. The results show that the central and southern regions of South Korea receive higher quantities of horizontal radiation, but not the northern areas.